Scabies Management Outcomes: Identification of Risk Factors for Treatment Success or Failure - Vanessa Azzolina; Franziska Schauer; Julia Felicitas Pilz; Alexander Zink; Kilian Eyerich; Caroline Pilz (Dermatology Practical & Conceptual)
Introduction: Scabies is a parasitic infectious skin disease classified as a neglected tropical disease by the World Health Organization in 2017. Currently, it is becoming a major challenge in high-income countries, with rapidly rising incidence and increasing reports about treatment failure.